2022
DOI: 10.31389/jltc.139
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality and the Quality of Life of Individuals with Intellectual Disability

Abstract: Context: Spirituality seems to form part of person-centred care planning and needs assessment of persons with intellectual disability. Yet, the role of spiritually in relation to their quality of life (QoL) has scarcely been investigated.Objective: This paper reports on an exploration of the extent to which spiritual belief and practice was linked to individuals' perception of quality of life in two types of care servicesone a faith-based provider, the other a non-faith based service.Method: A mixed-methods ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
0
0
Order By: Relevance
“…Although sample sizes in these studies tend to be small (<50 participants), in the work of Shogren and Rye (2005) 76% of the adults they interviewed with intellectual disabilities reported attending worship services and the majority confirmed that they believed in God and used positive coping strategies. Sango and Forrester-Jones (2022) discovered that participants valued the psychological benefits of church attendance and spiritual practices as well. "These practices not only enable individuals to connect with family and friends but also to connect with .…”
Section: The Role Of Spirituality and Religion In The Lives Of People...mentioning
confidence: 99%
“…Although sample sizes in these studies tend to be small (<50 participants), in the work of Shogren and Rye (2005) 76% of the adults they interviewed with intellectual disabilities reported attending worship services and the majority confirmed that they believed in God and used positive coping strategies. Sango and Forrester-Jones (2022) discovered that participants valued the psychological benefits of church attendance and spiritual practices as well. "These practices not only enable individuals to connect with family and friends but also to connect with .…”
Section: The Role Of Spirituality and Religion In The Lives Of People...mentioning
confidence: 99%